Performance Measurement and Evaluation Framework of Public Microtransit Service. Issue 12 (December 2021) - Hansen, Todd; Walk, Michael; Tan, Shuman; Mahmoudzadeh, Ahmadreza
This research project developed an evaluation framework and service standards for microtransit service at a metropolitan transportation authority. Microtransit provides an elevated level of service from traditional demand response, enabling more spontaneous travel and better connectivity to the fixed-route system, meaning microtransit service performance standards fit in between traditional demand response and fixed route. Microtransit neighborhood zones also serve distinct purposes depending on the operational and financial characteristics of a given zone. The purpose of this evaluation framework project was to determine the optimal performance measurement process for microtransit service. The research team developed the evaluation framework through gathering information from agency staff on current goals and objectives for microtransit, conducting an industry scan, and determining measurable metrics from available data sources. The project developed a typology of microtransit service zones, then created the evaluation framework using the performance measures applicable to agency goals. The research team conducted a final test of the framework at the six-month period of service to refine the measures as needed. Minimum standards and optimal goals were set for each performance measure based on system performance and agency goals for innovative service. The framework uses service standards and goals that are applicable to given types of neighborhood zones and distinct from baseline standards for fixed-route or other demand-responsive service. The evaluation framework can be integrated into transit agency service standards to measure the success of microtransit neighborhood zones and planning future service.